2023
DOI: 10.3390/pathogens12070912
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing Shows that African Swine Fever Virus Genotype IX Is Still Circulating in Domestic Pigs in All Regions of Uganda

Abstract: Blood samples were collected from pigs at six abattoirs in the Kampala, Uganda metropolitan area from May 2021 through June 2022, and tested for African swine fever virus. Thirty-one samples with cycle threshold values < 26 from pigs with different geographic origins, clinical and pathologic signs, and Ornithodoros moubata exposure underwent whole genome sequencing. The p72 gene was used to genotype the isolates, and all were found to be genotype IX; whole genome sequences to previous genotype IX isolates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…More studies are needed to confirm the reliability of the TK assay as an additional molecular diagnostic marker for African swine fever detection, particularly in low-resource countries where real-time PCR capabilities are limited. Acknowledged limitations of the study include the number of districts covered and the total number of samples processed may be insufficient to draw robust conclusions, especially given the geographic diversity of Uganda and virus circulation [ 35 ]. Future studies should consider the expansion of the study areas to include more districts and consider a larger sample size to draw inference for generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to confirm the reliability of the TK assay as an additional molecular diagnostic marker for African swine fever detection, particularly in low-resource countries where real-time PCR capabilities are limited. Acknowledged limitations of the study include the number of districts covered and the total number of samples processed may be insufficient to draw robust conclusions, especially given the geographic diversity of Uganda and virus circulation [ 35 ]. Future studies should consider the expansion of the study areas to include more districts and consider a larger sample size to draw inference for generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…The whole-genome sequencing of ASFV has been widely used for virus strain characterization. Over 200 ASFV genome sequences of different origins and variable virulence have been determined and deposited in GenBank [ 7 , 18 , 19 , 20 ]. Different types of ASFV genome variation have been identified including the gain or loss of MGF members, deletion or insertion of genomic fragments, variation in the numbers of repeat units in the tandem repeat sequences, polymer tract variation and single nucleotide variation.…”
Section: Introductionmentioning
confidence: 99%
“…ASFV is a large, structurally complex virus, harboring a large, double-stranded DNA genome of 180–190 kilobase (kb) pairs, which encodes more than 160 genes [ 2 ]; recently, all of these genes have been predicted structurally [ 3 ] and the proteome of ASFV was determined [ 4 , 5 ]. We recently reported that there are six unique genotypes of ASFV [ 6 ], with the pandemic genotype 2 strain (previously classified as genotype II) gaining the most attention, as it is currently causing diseases in domestic and wild boar in Europe, Asia, Western Africa, and the island of Hispaniola [ 7 , 8 , 9 , 10 , 11 , 12 ]. The genotype 2 strains are highly virulent and are severely affecting pork production across the globe.…”
Section: Introductionmentioning
confidence: 99%